Emancipatory Education from Western and Islamic Perspectives: The Relevance of Paulo Freire's Ideas to Contemporary Islamic Education - Dafarizi, Muhammad; Yumila; Rozi, Fahrur; Sari, Herlini Puspika (FITRAH: International Islamic Education Journal, 2025)
Abstract This study examines the relevance of Paulo Freire's liberation education concepts to contemporary Islamic education in Indonesia. In the context of globalization and technological transformation, Islamic education is still largely transmissive and hierarchical, causing students to be treated more as objects than active subjects of learning. The objectives of this research are: (1) to explore the relevance of Freire’s thought to the values of Islamic education; (2) to formulate an integrative pedagogical framework that combines Freire's principles of liberation with Islamic educational practices; and (3) to provide practical recommendations for Islamic educational institutions to create more participatory and reflective learning environments. The study employs a library research approach with content analysis of national scholarly literature published between 2019 and 2024, selected based on thematic relevance, publisher credibility, and full-text accessibility. The research instrument is a content analysis sheet categorizing operational indicators of each literature source. The research hypothesis posits that contextual application of liberation education principles in Islamic education will increase active participation, critical awareness, and social commitment among students compared to traditional methods. Findings indicate that Freire’s emphasis on dialogue, critical consciousness, and praxis aligns with Islamic educational principles, which position humans as moral, spiritual, and social beings. Integrating these paradigms enables the creation of a participatory and liberating Islamic education model that develops not only students’ intellect but also their moral and spiritual awareness. This study contributes theoretically by enriching the philosophy of Islamic education with critical and humanistic perspectives, and practically by offering a framework for Islamic educational institutions to design reflective, dialogic, and transformative curricula and teaching strategies. In conclusion, contemporary Islamic education can leverage Freire’s principles of liberation to cultivate a generation that is faithful, critical, and socially responsible.